Comparison of Whole-class Discussion and Task-based Activity: A Small-Scale Study - Farzaneh, Thoraya Abdullah (2020)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Thoraya Abdullah Farzaneh entitled, “Comparison of Whole-Class Discussion and Task-Based Activity: A Small-Scale Study”, submitted in May 2020. Thesis advisor is Dr. Alessandro Benati. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).